Design Of Website-Based Online Reservation And Queue Application At UPTD Puskesmas Kayen Kidul - Jayanto, Deni Luvi; Zuliana, Ni'matu; Poonwong, Prakasit; Dwitama Hidayat, Andra; Bin Djusmin, Vicky; Firmansyah, Roma; Mukti Lestari, Tri; Mulya Ike Ardila, Ninda (Journal Health Information Management Indonesian (JHIMI), 2024)
UPTD Puskesmas Kayen Kidul always prioritizes service to the community but has difficulty managing patient registration and queues because it does not have digital and online registration so patients are not optimal when there are many visits. A patient registration system design is required which can be used as a reference for building the system by the programmer. This research aims to review the availability of Standard Operating Procedures (SOP), system requirements in the Unified Modeling Language (UML) and design a user interface for website-based online reservations and queues. This type of research uses a qualitative descriptive approach with 2 registration officer respondents through interviews and then analyzing feature needs and data using SOPs with observation. The research results of the SOPs already exist and are appropriate, UML in the form of use cases, activity diagrams, sequence diagrams and class diagrams have been created and user interface requirements based on color, layout and controls have been realized and tested on officers.